(untitled) (Polis (Santiago), 2025)
We investigate the role of virtual social networks as spaces for political socialization in a context of recurrent conventional political action in Chile and its respective consequences. Fourteen young university students participated, who through semi-structured interviews, related their experiences on the use of social networks as sources of political information. The results indicate that digital platforms are considered an important source of political socialization in times of electoral decisions, despite the fact that their use entails certain risks associated with post-truth, such as disinformation, the emergence of fake news and the lack of control over this scenario. The participants recognized that their political stance is influenced by the information shared on these networks, stressing the importance of developing critical skills to discern about the content consulted and presented. We conclude that social networks are powerful tools to foster citizen participation and political engagement, but their effectiveness or risk depends on the citizenship education and digital training that young people receive in this regard as spaces for political socialization.